Stabilization of acenes: “Geländer”-pentacenes [data] - Ludwig, Philipp; Rominger, Frank; Freudenberg, Jan; Bunz, Uwe H. F. (Universität, 2024)
We report soluble tetrakis-biphenyl substituted pentacenes comprised of sp2 carbons and synthesized from pentacene-5,7,12,14-tetraone. Intramolecular Yamamoto coupling of two tetrakis(chlorobiphenylyl)pentacenes yields helical, doubly wrapped pentacenes, in which the quaterphenylene units solubilize the pentacenes and shield their central anthracene units to an unprecedented degree. The criss-cross-bridged pentacenes resist (photo)oxidation, Diels-Alder reactions and are much less reactive than TIPS-ethynylated pentacene. Extension of this concept might provide access to the larger acenes.
Finanziert durch: Deutsche Forschungsgemeinschaft (SFB): 1249, Deutsche Forschungsgemeinschaft: INST 40/575-1 FUGG, Deutsche Forschungsgemeinschaft: INST 35/1596-1 FUGG
Gesehen am 22.02.2024
Keywords: Forschungsdaten; Datenbank